1997
DOI: 10.1002/(sici)1097-4547(19970901)49:5<522::aid-jnr2>3.0.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Neurotrophin signal transduction in medulloblastoma

Abstract: The members of the neurotrophin family play key biological roles in the development of the nervous system. Based on studies initially in cell lines (e.g., the rat pheochromocytoma PC12 cells), neurotrophins have been found to be important mediators of proliferation, differentiation, and survival in the normal brain, but their role in brain tumors remains unclear. Since neurotrophins and neurotrophin receptors are frequently detected in biopsy samples of central nervous system medulloblastomas, efforts have bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 41 publications
1
6
0
Order By: Relevance
“…This concept of dual neurotrophin functions in different HF compartments is in line with recent findings that NGF and BDNF, which are primarily appreciated for their anti-apoptotic properties (24,25,88), can also induce apoptosis in several systems via interaction with p75NTR (73)(74)(75)(76)80). Since NGF is even capable of inducing apoptosis in medulloblastoma cells via stimulation of TrkA (78,93,94), it should be considered that BDNF and NT-4 may operate as proapoptotic signals for epithelial strand KCs during catagen. Whether apoptosis in individual KCs of the regressing HF is stimulated by BDNF or NT-4 not only varies among follicular KC subpopulations, but most likely also depends on the local concentration of neurotrophins and the receptor expression pattern, namely, the coexpression of Trk and p75NTR on the target cells (76,77,79).…”
Section: Discussionsupporting
confidence: 70%
“…This concept of dual neurotrophin functions in different HF compartments is in line with recent findings that NGF and BDNF, which are primarily appreciated for their anti-apoptotic properties (24,25,88), can also induce apoptosis in several systems via interaction with p75NTR (73)(74)(75)(76)80). Since NGF is even capable of inducing apoptosis in medulloblastoma cells via stimulation of TrkA (78,93,94), it should be considered that BDNF and NT-4 may operate as proapoptotic signals for epithelial strand KCs during catagen. Whether apoptosis in individual KCs of the regressing HF is stimulated by BDNF or NT-4 not only varies among follicular KC subpopulations, but most likely also depends on the local concentration of neurotrophins and the receptor expression pattern, namely, the coexpression of Trk and p75NTR on the target cells (76,77,79).…”
Section: Discussionsupporting
confidence: 70%
“…Since the ability of NGF to stimulate apoptotic cell death via interaction with TrkA was also shown previously (73,74) and neurotrophins could theoretically promote catagen via stimulation of Trk receptors abundantly expressed in the regressing HF compartments during catagen (17,18), followed by the release of other proapoptotic molecules like TNF-alpha, Fas-ligand, or TGF-␤ from Trk-positive cell populations, one can also envision p75NTRindependent pathways in the catagen stimulatory action of neurotrophins. However, our data that NGF, BDNF, or NT-3 fail to stimulate HF regression in p75NTR null skin ( Fig.…”
Section: Discussionmentioning
confidence: 75%
“…The expression of growth factors in gliomas has attracted a lot of interest because of their significance for regulation of growth and differentiation, thereby leading to new therapeutic interventions. Several studies reported that growth factors and their cognate receptors influence the induction or progression as well as the differentiation of neoplasms [5,17]. GDNF, a sequence-related member to the TGF-β superfamily, is expressed in primary cultured astrocytes of rats [28] and humans [22] and in activated macrophages and microglia [3], possibly playing a potent role in differentiation or proliferation.…”
Section: Discussionmentioning
confidence: 99%